Tribological Performance Optimization of Mg-WC Nanocomposites in Dry Sliding: A Statistical Approach - Banerjee, Sudip; Sahoo, Prasanta; Davim, J. Paulo (Frontiers in Materials, 2022)
Magnesium nano-composites reinforced with ceramic reinforcements have emerged as superior structural material for automotive applications due to their excellent specific properties. In this context, the current study aims to scrutinize the performance of Mg-WC nano-composites in tribological applications. The effect of various input parameters (wt.% of reinforcement, load and speed) on output responses (wear and coefficient of friction) is scrutinized using response surface methodology. Mg-WC nano-composites having varying weight percentage of WC are synthesized using ultrasonic treatment associated stir-casting technique. Typical characterizations of as-cast nano-composites are done using scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). SEM micrographs confirm homogeneous dissemination of fortified particles in base matrix while EDS confirm elemental composition. Analysis of variance (ANOVA) study is conducted to discover significant parameters affecting tribological performance. Surface plots and contour plots for tribological responses are also examined to observe interaction effects. ANOVA analysis on wear confirms that wt.% of WC and speed are utmost significant parameters whilst interaction between wt.% of WC and speed has significant influence. For coefficient of friction, all the input parameters are significant and interaction between wt.% of WC and load is utmost significant. Regression equations for response parameters are also developed. Additionally, desirability approach is considered to investigate both single and multiple objective optimization criterions of output parameters. Desirability function for both single and multi-optimization remains 0.9778, suggesting the presence of all input parameters within working limit. Predicted and experimental values of optimal setting possess close fit for the current study. Minimum wear is achieved when wt.% of WC is 1.73%, load is 40N and speed is 100 rpm. Minimum friction is obtained when wt.% of WC is 1.78%, load is 40N and speed is 100 rpm. Multi-optimization result yields that minimum value of wear and friction are achievable when wt.% of WC is 1.73%, load is 40N and speed is 100 rpm. Finally, worn surface of samples are examined to observe possible wear mechanisms.